The Relationship Between Family Communication and the Tendency of Postpartum Depression Reviewed from the Big Five Personality Traits in Postpartum Mothers - Darmawan, Sianawati; Noviekayati, IGAA; Evita Santi , Dyan (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The postpartum period is a transitional phase that can lead to a life crisis and increase the likelihood of postpartum depression (PPD) in some mothers. Symptoms include sadness, irritability, disturbed appetite, insomnia, and exhaustion. Family support, especially through communication, can help reduce the risk of PPD. Additionally, an individual's personality plays a role in coping with postpartum challenges, as explained by the Big Five Personality Traits Theory, which classifies personality into five dimensions: neuroticism, extraversion, openness to experience, conscientiousness, and agreeableness. This study aims to examine the relationship between family communication, the Big Five traits, and the tendency for PPD. A quantitative correlational approach was used, with questionnaires distributed to 60 subjects from four Midwifery Independent Practices. The results showed a significant negative correlation between family communication and the tendency for postpartum depression (t = -5.337, p = 0.000). This indicates that better family communication is associated with a lower likelihood of PPD. Additionally, significant differences were found in the Big Five dimensions in relation to PPD tendencies, with extraversion (t = -3.779, p = 0.000) and agreeableness showing strong correlations.